ALDOLASE A regulates invasion of bladder cancer cells via E‐cadherin‐EGFR signaling. Issue 8 (13th May 2019) - Li, Jianwei; Wang, Fang; Gao, Hongzhi; Huang, Sihuai; Cai, Fangzhen; Sun, Jianguo
Abstract: Glycolysis and glycogenesis are known to be tightly associated with cancer cell migration. However, their roles in bladder cancer have not been reported. In this study, ALDOLASE A (ALDOA) was identified in a coexpression network generated using glycolysis‐ and glycogenesis‐related genes in Kyoto Encyclopedia of Genes and Genomes. ALDOA was located in the central region in the network, and the cancer genome atlas (TCGA) data suggest that ALDOA expression levels are associated with viability in patients with cancer at the middle and late stages. Bladder cancer cell lines, T24 and RT4, were used to knockdown (sh) or overexpress (OE) ALODA to analyze its role. The sh‐ALDOA reduced cell viability, colony formation rate, and invasion cell number; while OE had an opposite effect compared with sh‐ALDOA. Further, the sh‐ALDOA expression induced E‐cadherin level while reduced N‐cadherin and vimentin levels. The OE cells reduced E‐cadherin and induced N‐cadherin and vimentin levels. In addition, epidermal growth factor receptor (EGFR), mitogen‐activated protein kinase (MAPK), and AKT serine/threonine kinase (AKT) phosphorylation levels are all reduced in sh‐ALODA while activated in OE cells compared with the control group. But either sh‐ALODA or OE did not change total protein levels of EGFR, MAPK, and AKT. To further analyze E‐cadherin function in ALDOA regulation on bladder cancer cells, sh‐ALDOA and sh‐E‐cadherin were cotransfected in T24 and RT4 cells. The results indicated that sh‐ALDOA and sh‐E‐cadherin expressions eliminated sh‐ALDOA function, resulting similar cell viability, colony formation rate, and invasion cell number with control group. Also, sh‐ALDOA and shE‐cadherin expressions increased EGFR, MAPK, and AKT phosphorylation levels; and the levels were similar to the control group. But, sh‐ALDOA and sh‐E‐cadherin expressions did not change N‐cadherin and vimentin levels, which maintain similar levels with sh‐ALDOA‐expressing cells. Taken together, these results suggest that ALDOA might play an important function in bladder cancer and its action may be though E‐cadherin‐EGFR signaling. Abstract : The glycolysis roles in bladder cancer have not been reported. In this study, ALDOLASE A (ALDOA) was identified in a co‐expression network generated using glycolysis‐ and glycogenesis‐related genes in Kyoto Encyclopedia of Genes and Genomes. ALDOA was associated with viability of patients with cancer, and its action might be through E‐cadherin‐EGFR signaling.